Home haemodialysis update. (2nd March 2019) - Palmer, Nicholas
Abstract : In 2018, Nicholas Palmer lost his second transplant, later turning to home haemodialysis. In this article, he considers the highs and lows of the latest phase of his treatment, as well as considering issues facing kidney patients in the UK